Panel Cointegration Tests on the Fiscal Sustainability of German Laender - Heiko T. Burret; Lars P. Feld; Ekkehard A. Köhler (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper provides new evidence on the sustainability of public finances in German states (Laender) by exploiting a newly compiled database covering the years 1950]2011. Unlike previous studies on Germany, we analyze fiscal sustainability by applying gsecond generationh panel cointegration techniques. A unique identification strategy for the selection of sub]panels improves the robustness of panel cointegration tests and reveals that Laender finances are hardly sustainable.
Keywords: H62; H77; H72; 330; fiscal sustainability; federalism; unit root; panel cointegration